PERAN TWITTER DALAM DIGITAL CUSTOMER RELATION MANAGEMENT DI INDUSTRI PERBANKAN - Setyadi, Dyama Khazim (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2019)
In a digital transformation era, various companies are competing to change communication patterns with consumers, so that consumers are expected to be more loyal to the company. One transformation is social media optimization to build a conversation with consumers. The use of Twitter as one of the social media platforms in Indonesia by the company is currently considered as something that is needed, even though Twitter's popularity is not as high as Facebook, Instagram, or Youtube. With 22 million users in Indonesia, Twitter is one channel for companies in customer relations, one of which is as part of the customer relationship management channel. Using the netnographic method, this study analyzes the role of Twitter as part of a company's CRM channel in the digital age, especially in the banking industry, as well as its implications for consumers. To cite this article (7th APA style): Setyadi, D. K. (2019). Peran Twitter dalam Digital Customer Relationship Management di Industri Perbankan [The Role of Twitter in the Digital Customer Relationship Management in Banking Industry]. Journal Communication Spectrum, 9(2), 110-124. http://dx.doi.org/10.36782/jcs.v9i2.1952